Plasmonics: Rational Assembly of Optoplasmonic Hetero‐nanoparticle Arrays with Tunable Photonic–Plasmonic Resonances (Adv. Funct. Mater. 6/2014). (February 2014) - Hong, Yan; Qiu, Yue; Chen, Tianhong; Reinhard, Björn M.
<x xml:space="preserve">Abstract</x> Template‐guided self‐assembly facilitates the fabrication of optoplasmonic hetero‐nanoparticle arrays that contain metallic and dielectric nanoparticles or nanoparticle clusters at pre‐defined lattice sites. On page 739, the integration of nanoparticles with different compositions at programmable positions into an array by B. M. Reinhard and co‐workers generates hybrid electromagnetic materials with new degrees of freedom for tailoring near‐ and far‐field optical responses as well as enhancing light–matter interactions through synergistic electromagnetic interactions between the building blocks. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>